China’s English-Language Journals in Human and Social Sciences - Li, Mengyang; Yang, Rui (International Higher Education, 2019)
Since the 2000s, China has been establishing English-language academic journals at a fast pace to further internationalize research. Reporting findings from an investigation on the current state of such journals in the humanities and social sciences, this article shows the great challenges that they face in the hierarchical global structure of knowledge production. Struggling between international ambition and local commitment, these journals try to balance realistic strategies to enhance international impact with orientation to Western research agendas and their long-term commitment to empowering Chinese researchers to become global.